Is Earnings Quality Influenced by Environmental, Social, and Governance (ESG) Disclosures? Evidence from the Alternative Capital Market of Thailand - Suttipun, Muttanachai; Pratoomsuwan, Thanyawee (วารสารนวัตกรรมธุรกิจ การจัดการ และสังคมศาสตร์, 2024)
The study investigates (1) the level of environmental, social, and governance (ESG) disclosures in annual reports of Market for Alternative Investment (MAI) listed firms during 2017 to 2021, and (2) test for the impact of ESG disclosures on earnings quality. One hundred and twenty firms from the MAI were used as samples in this study (600 firm-year observations). We employed Content analysis to quantify the amount of the ESG disclosures, while an Extended Modified Jones of Yoon’s model was used to measure corporate earnings quality. Our results show that governance was the most common ESG disclosure in the annual report of MAI firms during the period being studied, followed by social disclosure and environmental disclosure respectively. There was an increasing trend of environmental, social, and disclosures between 2017 to 2021. Moreover, the study found a significant and negative impact of social disclosure on earnings management, suggesting that firms with higher levels of social disclosure are likely to engage in less earnings management. Conversely, the positive association between environmental and governance disclosure and earnings quality could imply less engagement in earnings management activities.